Coaching Small Industries Kerupuk Kawasan Wisata Ujungpangkah Kabupaten Gresik - Tri Ratnawati; I Nyoman Lokajaya (Universitas Negeri Surabaya, 2021)
Raw materials for making crackers in the form of fish are very abundant in this village and most people make a living as fishermen and fish pond farming. Fish used as raw material for making crackers are payus fish and laosan. The cracker industry produced by most of the craftsmen in Ujung Pangkah sub-district, Gresik Regency, the majority are sold in the form of 'raw crackers' at very cheap prices, simple packaging, less attractive shapes and marketed in the local area, so the product quality must be improved. Fish crackers are crackers whose ingredients consist of a mixture of flour and fish meat. Many types of fish can be used as a basis for making crackers. Payus fish (Elops hawaiensis) is one of the predatory fish species of small fish and crustaceans in ponds. The existence of this fish is quite abundant so that it can be used as a product that can be consumed by the community. Coaching assistance and in the form of providing manual dough cutting machine tools accelerate the production process and production cost efficiency. Assistance with the production process has been carried out through quality control, micro marketing (Instragram and Facebook), financial management reporting through microfinance accounting processes.